Teaching Disciplinary Writing as Social Practice: Moving Beyond ‘text-in-context’ Designs in UK Higher Education - Green, Simon John (Journal of Academic Writing, 2016)
This paper concerns the teaching of disciplinary academic writing in Higher Education in the UK and is motivated by the need to identify an EAP instructional design that will facilitate student writers’ engagement with disciplinary writing as a situated social practice. In the paper I describe and critique what I characterise as a ‘text-in-context’ genre-based pedagogy influential in EAP provision in the UK, and then sketch out the broad parameters of a ‘social practice’ instructional design, enactable within the context of UK Higher Education.